Eliminasi Vektor Demam Berdarah Dengue melalui Penyuluhan dan Pemasangan Ovitrap di Kelurahan Puuwatu Kecamatan Puuwatu - Reni Yunus; Supiati Supiati; Theosobia Grace Orno (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2021)
Dengue Hemorrhagic Fever (DHF) is a contagious disease that occurs due to infection with the Dengue virus, which is carried by the Aedes aegypti mosquito as the main vector. Research on ovitrap placement in DHF endemic areas has been conducted before in Kendari City. The results of this research need to be implemented in the form of community service activities. This community service activity aims to increase stakeholder understanding through dissemination of research results in the Puuwatu village area, increase public knowledge about the concept of handling dengue fever and its prevention, and to install ovitraps to find out how much success ovitrap has in reducing adult mosquito density. Post-test results after counseling about DHF showed an increase in public knowledge about DHF and its prevention. Ovitrap observations posted on 50 houses of Puuwatu village residents showed that ovitrap installed in all zones contained positive ovitrap eggs of Aedes sp.